Determinación de la calidad del suelo utilizado en pastoreo de bovinos en el área verde del barrio Chantilin Grande, cantón Saquisilí, provincia de Cotopaxi en el año 2022 - Cuyo Pilalumbo, Jefferson Stalyn (2022)
Into present research, it was made the caused effects determination by bovine grazing for determining the Green area soil quality from Chantilin Grande district, Saquisili canton, Cotopaxi province, corresponding to the altitude floor at 3126 m.s.n.m. This place was established the evironmental diagnosis, soil physicochemical factors analysis and the infiltration determination. The used research methodology is a mixed approach, which frames qualitative and cuantitative characteristics, since the research work resulted in the experimental analysis data at the laboratory level, and data analyzed from different digital and bibliographic repositories. The biodiversity main result was determined, what the intervened area lost more than 75%, its vegetation. In the soil chemical factors analysis, they are based on the results from laboratory, the same one that serves to determine the soil quality, the got results inidicate, what there is not much difference some chemical factors between the intervened and non-intervened plots, however into conductivity there is a 147 µs/cm difference, into humidity there is a 11.02% difference and into DQO a 29.8 mg/kg difference. These are the factors, what present the greatest alteration in the data. The infiltration results are based on the Muntz technique, they show, what there is a 210mm/h difference between the intervened and non-intervened plots. It can be concluded, what grazing has multiple consequences, such as the foliage consumption, affecting the plants development and reproduction, the species alteration and plant cover, also the bovines trampling modifies the soil surface structure and reduces the infiltration capacity, water inside it, increasing surface flow and erosion. The conservation proposal was proposed to make a plan for sustainable livestock and thus, mitigating the degradation these soils and enriching the people knowledge from Chantilin Grande district.